Legitimasi Hukuman Mati: Perlukah Mandatory Consular Notification Antar Negara? - Fatriani, Lendra; Sipahutar, Bernard (Faculty of Law, Universitas Jambi, 2022)
This article questions how the Mandatory Consular Notification practice applied by the Kingdom of Saudi Arabia to Indonesia in rescuing workers sentenced to death. Mandatory Consular Notification is the right to obtain information and access related to state representatives for their citizens and citizens' rights to state representative staff. This is the main guideline in the management of international relations which has been regulated in Article 36 and Article 37 of the 1963 Vienna Convention. In its implementation, the Kingdom of Saudi Arabia does not carry out Mandatory Consular Notification in accordance with applicable regulations. Therefore, Indonesia needs to ensure legal protection efforts for its workforce by conducting a Memorandum of Understanding with the Kingdom of Saudi Arabia. In addition, Indonesia also needs to seek other legal steps, especially in the form of agreements in order to create legal certainty between the state parties.